2022
DOI: 10.1097/md.0000000000030637
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of sleep disturbance in adults with underlying health conditions during the ongoing COVID-19 pandemic

Abstract: To determine the prevalence of sleep disturbance during the coronavirus disease 2019 (COVID-19) pandemic among US adults who are more vulnerable to complications because of age and co-morbid conditions, and to identify associated sociodemographic and psychosocial factors. Cross-sectional survey linked to 3 active clinical trials and 2 cohort studies, conducted between 11/30/2020 and 3/3/2021. Five academic internal medicine practices and 2 federally qualified health centers. A total of 715 adults ages 23 to 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(85 reference statements)
1
5
0
Order By: Relevance
“…These results corroborate those of previous reports from different countries and with patients in different age ranges, such as studies conducted in Israel (age range: 60 to 92 years), 7 Bangladesh (age range: 18 to 75 years), 9 the United States (age range: 23 to 91 years), 11 and Japan (age range: 20 to 86 years), 13 which also reported worsening sleep quality during the pandemic. More comprehensive research, such as the international cross-sectional study by Mandelkorn et al, 17 which analyzed the sleep quality of 2,562 adults with a mean age of 45.18 AE 14.46 years from 49 countries, reported that 40% of the sample revealed a decrease in sleep quality during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate those of previous reports from different countries and with patients in different age ranges, such as studies conducted in Israel (age range: 60 to 92 years), 7 Bangladesh (age range: 18 to 75 years), 9 the United States (age range: 23 to 91 years), 11 and Japan (age range: 20 to 86 years), 13 which also reported worsening sleep quality during the pandemic. More comprehensive research, such as the international cross-sectional study by Mandelkorn et al, 17 which analyzed the sleep quality of 2,562 adults with a mean age of 45.18 AE 14.46 years from 49 countries, reported that 40% of the sample revealed a decrease in sleep quality during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…A cross-sectional study was performed using a convenience sample of 290 older adults (aged ≥ 60 years) from 61 Brazilian cities. Based on previous studies 10 11 that reported that between 20% and 29% of older adults experienced poor sleep quality or deterioration of sleep quality during the pandemic, the sample size was estimated considering a prevalence of 25% in older adults with sleep problems, a sampling error of 5%, and a 95% confidence level. As such, the minimum sample size was calculated to be of 289 subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, no significant difference was found in the mean age of individuals, gender, or BMI based on sleep quality. Studies have been done examining sleep as it relates to age in PLWH [5,37,38], and gender [39,40]. There have been mixed results on both variables in past research, and this could warrant further examination.…”
Section: Discussionmentioning
confidence: 99%
“…We included five different sleep disturbances: 1) sleep disorders (sleep problems in 19 studies using self-constructed items ( Amerio et al, 2023 ; Collinge & Bath, 2023 ; Corley et al, 2021 ; Gokseven et al, 2022 ; Gustavsson & Beckman, 2020 ; Ikeda et al, 2022 ; Kapusta et al, 2023 ; Makizako et al, 2021 ; Nakai et al, 2022 ; Okely et al, 2020 ; Osiogo et al, 2021 ; Paiva et al, 2021 ; Perelman, Xavier, & Barros, 2022 ; Rodríguez-Gómez et al, 2022 ; Sampaio Brito, de Lima, Mascarenhas, Mota, & Leite, 2021 ; Sapara et al, 2021 ; van der Velden, Marchand, Das, Muffels, & Bosmans, 2022 ; Yilmaz & Onal, 2023 ; Yurumez Korkmaz et al, 2021 ) and poor sleep quality in seven studies using Pittsburgh sleep quality index (PSQI) and the Patient-Reported Outcomes Information System (PROIS) ( Amicucci, Salfi, D'Atri, Viselli, & Ferrara, 2021 ; Bhat, Mir, Hussain, & Shah, 2020 ; Garcia Carlini et al, 2023 ; Kantor, Kantor, Fortgang, & Pace-Schott, 2022 ; Kim et al, 2022 ; Udeh-Momoh et al, 2021 ; Wang et al, 2021 ); 2) short sleep duration <7 h (three studies) ( Amerio et al, 2023 ; Mistry et al, 2021 ; Rodríguez-Gómez et al, 2022 ) and long sleep duration ≥9 h (two studies) ( Mistry et al, 2021 ; Rodríguez-Gómez et al, 2022 ); 3) insomnia symptoms (three studies using self-constructed items ( Savci et al, 2021 ; Schou-Bredal et al, 2021 ; Xu, Li, Zhu, & Zhong, 2022 ) and 11 studies using the insomnia severity index (ISI) or the Athens insomnia scale (AIS) ( Al-Mutawa & Al-Mutairi, 2021 ; Amicucci et al, 2021 ; Christodoulou et al, 2023 ; Dale, Budimir, Probst, Stippl, & Pieh, 2021 ; Humer, Schaffler, Jesser, Probst, & Pieh, 2022 ; Li et al, 2022 ; Parlapani et al, 2020 ; Philip et al, 2020 ; Pieh et al, 2021 ; …”
Section: Methodsmentioning
confidence: 99%